A curing Bible: the atmosphere of the group when using the Bible in bibliotherapeutic work - Alatalo, Kirsimarja (Journal of poetry therapy, 2025)
This paper is based on research of the experience of adults participating in one bibliotherapeutic developing group, which divides that writing from the Bible and sharing the texts in small groups increases joy, enthusiasm and reflexivity of self-experience. It discusses the rewriting of the Bible verses through poems, focusing in particular on two different poetic forms 'tanka' and 'pantoum'. The poems helped to process words into sentences, create something new and at the same time the writers were able to verbalize the unspoken. The material of the study was collected from the Bibliotherapy Group and participants ranged in age from 31 to 80. I focused in particular on group interaction, its therapeutic significance, and the relevance of the Bible texts to authors. Interactivity became a very important aspect in the writing group. Sharing your own text with others by reading aloud increased group spirit.